2022
DOI: 10.3390/nu14214484
|View full text |Cite
|
Sign up to set email alerts
|

The Interactive Effects of Severe Vitamin D Deficiency and Iodine Nutrition Status on the Risk of Thyroid Disorder in Pregnant Women

Abstract: Thyroid dysfunction is associated with both vitamin D deficiency and iodine; however, it is unclear whether they interact. This study aimed to investigate whether and to what extent the interactions between vitamin D and iodine contribute to the risk of thyroid disorder. Participants (n = 4280) were chosen using multistage, stratified random sampling from Shanghai. Fasting blood was drawn for the 25(OH)D and thyroid parameter tests. Spot urine samples were gathered to test for urine iodine. To evaluate the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Briefly, pregnant women who had lived in Shanghai for at least six months in the past year and who had established a healthy record at the local community health service center during different trimesters (first trimester ≤12 gestational weeks (GW), the second trimester (13–27 GW), and the third trimester (≥28 GW)) were recruited. The inclusion criteria for all pregnant women and detailed information about the study cohort, the study sites, and characteristics of the study group have been previously reported [ 24 , 25 ]. The first round of data collection took place from April 2017 to October 2017, during which pregnant women were enrolled in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, pregnant women who had lived in Shanghai for at least six months in the past year and who had established a healthy record at the local community health service center during different trimesters (first trimester ≤12 gestational weeks (GW), the second trimester (13–27 GW), and the third trimester (≥28 GW)) were recruited. The inclusion criteria for all pregnant women and detailed information about the study cohort, the study sites, and characteristics of the study group have been previously reported [ 24 , 25 ]. The first round of data collection took place from April 2017 to October 2017, during which pregnant women were enrolled in the study.…”
Section: Methodsmentioning
confidence: 99%